Diagnosis and treatment of cervical cancer: barriers faced by women during the Covid-19 Pandemic - Cruz, Francine Meira da; Sartor, Silvia Francine; Arzuaga-Salazar, María Angélica; Wall, Marilene Loewen; Mercês, Nen Nalú Alves das (O Mundo da Saúde, 2024)
The objective of this study was to understand the healthcare experiences and barriers faced by women with cervical cancer during the COVID-19 pandemic. This is an exploratory, qualitative, and multiple-case study research. Nine women with cervical cancer participated, and the content analysis technique was used. The different care trajectories within health services and the search for cancer diagnosis and treatment were evident. In all trajectories mentioned, there was no call for a cytopathological examination of the cervix. One of the outstanding aspects was the time between diagnosis and the start of treatment, which varied from 15 to 150 days among the women. Considering the trajectories uniquely in the health care system, those were different during the COVID-19 pandemic. Some barriers made it problematic to control and treat cancer. This study allows the understanding of trajectories and practices in the different logics expressed, through which the principles of comprehensiveness and resolution in health can be questioned. Thus, it supports an evaluative practice in health that privileges the experience of health or illness, as well as users’ seeking for care.